Self Services And Monitoring Of Weak Heart Disease Based On The Internet Of Things And Mobile App Using Certainty Factor - Somantri Somantri; Ikhsan Fazriawan; Adinda Laila Putri; Rafika Ariaty Maulani (Universitas Medan Area, 2022)
Heart disease can be suffered by anyone regardless of age and gender. Heart disease can be caused by many things, such as unhealthy lifestyles (smoking), as well as heredity. Low self-awareness of someone with weak heart disease to monitor their heart health regularly. To diagnose weak heart disease, this system uses the Certainy Factor method. With this method, patients can find out the results of the decision whether the patient is at risk of developing weak heart disease or heart health conditions in normal circumstances. This method can provide comparative results (and decision results) of several parameters (tested), one of which is the heart rate parameter. Therefore, the authors build a mobile application system with the concept of service and monitoring of weak heart disease named